Matching strategies of teachers and schools in general equilibrium - Tom Ahn (IZA Journal of Labor Economics, 2015)
I use a structural matching model, North Carolina public school data, and a survey of teachers' career plans to analyze schools' and teachers' behaviors in the teacher transfer market. Results show that mid-career teachers with better pre-service qualifications are the most eager to search, different types of teachers and schools have different search strategies, and the market is turbulent, characterized by search friction and large movements of teachers to better, worse, or comparable schools. The market is not as stable and orderly as it may first appear. Simulations show that simple policies to direct teacher transfers are at best inefficient.
Keywords: I24; J48; J62; 330; Matching; Teacher transfers; Ability sorting